“Ingsung Titip Tajug Lan Fakir Miskin” Budaya Mentifak Etnik Cirebon Dikaji Dari Dimensi Etnopedagogi - Mauly Rahadiani; Aninda Utari Pertiwi; Fitriani Tri Rahayu; Iin Wariin Basyari; Auliya Aenul Hayati (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to identify the values of local wisdom in the mentifact culture of the Cirebon Ethnic saying